2003
DOI: 10.1111/j..2003.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Scorecard Use in New Zealand Government Departments and Crown Entities

Abstract: RESEARCH & EVALUATIONWhile the concept of a balanced scorecard (BSC) has been extensively documented, there is limited research on the application of the balanced scorecard in a public sector environment and in New Zealand. This article examines how the BSC is being used as a performance management system, a strategic management system and to discharge external reporting obligations in three New Zealand public sector organisations. The findings are relevant to both the academic community and managers by highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 7 publications
3
39
0
6
Order By: Relevance
“…These findings are not inconsistent with other studies that have suggested that performance indicators used in the public and health sectors do not provide relevant information to position the organisations for future challenges. 3,13 The literature defines three main phases in the development of performance monitoring: an initial focus on the financial perspective, moving to multi-dimensional performance measurement frameworks (such as the balanced scorecard), and more recently, a greater link to realisation of strategy. 14 The balanced scorecard, with a 'balance' of financial, operational and customer satisfaction indicators, as a foundation to strategy maps, has been identified as an effective tool to monitor and improve organisational performance.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not inconsistent with other studies that have suggested that performance indicators used in the public and health sectors do not provide relevant information to position the organisations for future challenges. 3,13 The literature defines three main phases in the development of performance monitoring: an initial focus on the financial perspective, moving to multi-dimensional performance measurement frameworks (such as the balanced scorecard), and more recently, a greater link to realisation of strategy. 14 The balanced scorecard, with a 'balance' of financial, operational and customer satisfaction indicators, as a foundation to strategy maps, has been identified as an effective tool to monitor and improve organisational performance.…”
Section: Discussionmentioning
confidence: 99%
“…[55,56]). These various forms of tools and measures have been shown to have an impact on organizational goals and strategies, as well as reporting for public accountability [57,58]. An important area of investigation is how the tools are used, what the assumptions in them are, and how institutions and organizations are affected by these systems [59].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Griffiths (2003), in examining the BSC adoption in three New Zealand public sector organizations, report that none of the case organizations has implemented a BSC fully because causal linkages between the measures in the four BSC perspectives have not been established [9]. Chan (2004), in his survey on using the BSC in municipal governments of the USA and Canada, note that there is only limited use of the BSC for performance measurement [3].…”
Section: The Balanced Scorecardmentioning
confidence: 99%